PENDIDIKAN KARAKTER KI HADJAR DEWANTARA: STUDI KRITIS PEMIKIRAN KARAKTER DAN BUDI PEKERTI DALAM TINJAUAN ISLAM - Muthoifin Muthoifin; Mutohharun Jinan (Universitas Muhammadiyah Surakarta, 2015)
What an importance of character, Ki Hadjar makes it as a soul from the concept of his education. Even the government admitted, almost all national educational concepts referring to his idea. the focus of this issue is how the concept of Ki Hadjar's character in the Islamic view. The method used is historical approach, by the technique of content analysis, descriptive and comparative. The data is analyzed to be conclusion from the existing phenomenon. The results of the study, Ki Hadjar's idea about the character is not found the base that is closely related to faith, but rather stands on a universal national identity, it can be seen that the Ki Hadjar wants the Indonesian nation has a good attitude and personality and remain to stand on the personality of the Indonesian nation that has a distinctive culture and personality. While the characters in Islam can not be separated with monotheism and faith. Keywords: character; Ki Hadjar Dewantara; budi pekerti; Islam.